2014
DOI: 10.3386/w20648
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Short Term Exposure to Ambient Air Pollution on Cognitive Performance and Human Capital Formation

Abstract: Cognitive performance is critical to productivity in many occupations and potentially linked to pollution exposure. We evaluate this potentially important relationship by estimating the effect of pollution exposure on standardized test scores among Israeli high school high-stakes tests (2000)(2001)(2002). Since students take multiple exams on multiple days in the same location after each grade, we can adopt a fixed effects strategy estimating models with city, school, and student fixed effects. We focus on fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
116
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 20 publications
2
116
2
2
Order By: Relevance
“…Greater exposure to fine particles is associated with lower intelligence and diminished performance over a range of cognitive domains (Suglia et al, 2008;Power et al, 2011;Weuve et al, 2012). Consistent with this epidemiological evidence, a recent study of Israeli teenagers found that students perform worse on high-stakes exams on days with higher PM levels (Lavy et al, 2014).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Greater exposure to fine particles is associated with lower intelligence and diminished performance over a range of cognitive domains (Suglia et al, 2008;Power et al, 2011;Weuve et al, 2012). Consistent with this epidemiological evidence, a recent study of Israeli teenagers found that students perform worse on high-stakes exams on days with higher PM levels (Lavy et al, 2014).…”
mentioning
confidence: 72%
“…Exposure could impair productivity through changes in cardiovascular and lung functioning (Seaton et al, 1995), irritation of the ear, nose, throat, and lungs (Pope, 2000), as well as through direct impacts on cognitive performance (Lavy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution can also lower cognitive ability, alter emotions, increase anxiety, and have other psychological effects (Lavy, et al, 2014;Pun et al, 2016) which would affect the performance of both physical and knowledge workers. All of these effects can be compounded by spillovers to other workers (Arnott et al, 2005, Chapter 4).…”
Section: Pollution and Productivitymentioning
confidence: 99%
“…A few other papers examine pollution's effect on performance in other environments. Air pollution has been found to increase students' absences (Currie et al, 2009) and their cognitive performances and test scores (Lavy, et al, 2014). It also has negative effects on short-run performance of outdoor athletic participants including soccer players (Lichter et al, 2015), marathon runners (Fu and Guo, 2016), and baseball umpires (Archsmith et al, 2016).…”
Section: Pollution and Productivitymentioning
confidence: 99%
“…Moreover, since less advantaged individuals live in more 4 For example, Hanna and Oliva (2011) examine labor supply, while Graff-Zivin and Neidell (2013) study labor productivity. Studies also show that contemporaneous pollution exposure can affect human capital accumulation by increasing school absenteeism (Ransom and Pope, 1992;Gilliland, Berhane, Rappaport, Thomas, Avol, Gauderman, London, Margolis, McConnell, Islam, et al, 2001;Currie, Hanushek, Kahn, Neidell, and Rivkin, 2009), and impairing cognitive performance on high-stakes tests (Lavy, Ebenstein, and Roth, 2012). There is also a possibility that pollution can affect adult income if parents have to forego work to take care of asthmatic children (Currie, Hanushek, Kahn, Neidell, and Rivkin, 2009).…”
Section: Introductionmentioning
confidence: 99%